2020
DOI: 10.31486/toj.19.0093
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls and Safeguards in Industry-Funded Research

Abstract: Background: Physicians should follow ethical principles in their relationships with industry and be mindful that such relationships-if they are perceived as conflicts of interest-can undermine trust in the patient-physician relationship. Methods: By identifying potential pitfalls and safeguards that can help prevent problems, this article focuses on ensuring that physician-industry relationships do not result in ethical transgressions or cause damage to doctor-patient relationships. Results: Patient trust in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…27 Appropriate safeguards are needed to ensure that research addresses the most important and relevant questions, that results are available even when they do not support the use of a product produced by the funding company, that populations studied reflect those of the patients we treat, that the most rigorous approaches are applied, that studies have the appropriate power to address the question posed, and that conclusions are presented in an unbiased manner. 28,29 To address these concerns, the FDA has been providing increasingly detailed guidance for industry to conduct clinical trials. Furthermore, journal editors have elevated the reporting standard to increase the rigor and transparency of the research being published.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…27 Appropriate safeguards are needed to ensure that research addresses the most important and relevant questions, that results are available even when they do not support the use of a product produced by the funding company, that populations studied reflect those of the patients we treat, that the most rigorous approaches are applied, that studies have the appropriate power to address the question posed, and that conclusions are presented in an unbiased manner. 28,29 To address these concerns, the FDA has been providing increasingly detailed guidance for industry to conduct clinical trials. Furthermore, journal editors have elevated the reporting standard to increase the rigor and transparency of the research being published.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…There are myriad reasons why an AIP may fail including conflict between stakeholders, overpromising, over/under budgeting, unclear or changing aims, poor communication, inadequate governance, lack of a troubleshooting mechanism, milestones not met, failed deliverables, loss of marketability and/or commercialization, and an undesirable scandal. 55 , 56 , 57 , 58 …”
Section: Recommendations For Successful Partnershipsmentioning
confidence: 99%
“…A do-not-attempt resuscitation (DNR) order is a legal order that allows natural death. 4 , 5 Steinhauser et al 5 found that >90% of patients perceive that at the end of life, individuals need freedom from pain, freedom from shortness of breath, freedom from anxiety, and freedom to be treated as a whole person.…”
Section: Introductionmentioning
confidence: 99%